The Effect Of The Marketing Mix On Sales Rate At Ayam Keprabon Restaurant - Fakhry Adam Prayogo; Rayhan Gunaningrat; Indra Hastuti (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
In this study has the aim to determine the effect of marketing mix on sales levels at Ayam Keprabon Restaurant, using a sample size taken totaling 100 people from consumers of Ayam Keprabon Restaurant. The sampling technique uses purposive sampling, data is taken using a questionnaire measured by a Likert scale. This study used multiple linear regression analysis. At this time the marketing mix is the key to marketing in a company that can increase the level of sales. Based on the theoretical foundation and accompanied by the results of the analysis it can be concluded that, Food Quality has a significant effect on the Sales Level, Service Quality does not have a significant effect on Sales Level, Price has no significant effect on Sales Level, Physical efidence does not have a significant effect on Sales Level, Process does not have a significant effect on sales level, Place or Distribution Channel has a significant effect on sales level. Food quality, service quality, price, physical efidence, process and place together have a simultaneous effect on the variable Sales Level in Ayam Keprabon restaurant.